Convergence Analysis of Economic Growth in South Kalimantan - Sopiana, Yunita; Mursinto, Djoko; Sugiharti, Lilik (Universitas Airlangga, 2022)
The objectives of this research are 1) testing and analyzing the level of sigma convergence in South Kalimantan; 2) testing and analyzing the convergent beta, including the absolute beta convergence and conditional beta convergence. This study uses static panel data covering 13 regencies/cities in South Kalimantan observed between 2010 and 2019. The data analysis uses the ordinary least square (OLS) regression model. The results showed a sigma convergence marked by a declining variation coefficient in each regency/city. The absolute beta and conditional beta also converged. Poor areas' economic growth is faster than the prosperous regions so they catch up. There has to be close coordination between the central and local governments in formulating policies in handling government and private investment and improving workers' productivity in the agricultural and mining sectors in South Kalimantan.